USE OF MONOCLONAL ANTIBODIES TO HUMAN CYTOKINES IN DIAGNOSTIC AND ANALYTICAL STUDIES - Akhmedova V.A.; Krailo O.O; Myslynska O.I.; Sokolenko V.M.; Popova V.O.; Podlutska O.O.; Lutsenko T.M. (Biotechnologia Acta, 2024)
The use of human monoclonal antibodies in diagnostics and analytical studies is determined by the rapid development of technologies and approaches in the field of immunology and clinical laboratory diagnostics. Cytokines, as biologically active substances, play a key role in the regulation of immunity, inflammation and other physiological processes. The use of monoclonal antibodies to cytokines provides an opportunity to accurately determine their concentration and study the interaction with other molecules in clinical studies. The development of new diagnostic methods and analytical studies using monoclonal antibodies opened up prospects for increasing the accuracy and sensitivity of the determination of various diseases. This is especially important in the context of medicine, where accurate diagnosis becomes fundamental for choosing the optimal method.